2017
DOI: 10.18203/2319-2003.ijbcp20173752
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the pattern of antibiotic use in a tertiary care hospital

Abstract: Background: Indiscriminate use of antimicrobials is rampant throughout India, and this is a matter of serious concern. There are several reports linking antibiotic usage to bacterial resistance. Towards addressing this problem, community wise surveillance needs to be undertaken to monitor antibiotic exposure including their misuse. This study was meant to assess the extent and pattern of antibiotic use in a tertiary care facility. Methods: Subjects for study were patients attending a suburban hospital in centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…This is lower than the WHO standard value (100%). Moreover our values are lower comparing with the various other Indian studies conducted by Priyadharshini et al, 35 (62.5%) Mani et al, 37 (69%) and Pradeep kumar et al, 36 (91.48%). The Essential Medicine List (EML) or Essential Drug List is intended to satisfy the major health care needs of the majority of the population.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…This is lower than the WHO standard value (100%). Moreover our values are lower comparing with the various other Indian studies conducted by Priyadharshini et al, 35 (62.5%) Mani et al, 37 (69%) and Pradeep kumar et al, 36 (91.48%). The Essential Medicine List (EML) or Essential Drug List is intended to satisfy the major health care needs of the majority of the population.…”
Section: Discussioncontrasting
confidence: 78%
“…Moreover, the value was also higher compared to the findings from one of the South Indian studies by Priyadharshini et al, 35 (2.5) and also lesser than that of study conducted by Pradeep kumar et al, 36 (3.53). The percentage of encounters with antibiotics is 4.50% which lies within WHO standard value (normal range <30%), but lower when compared with studies of Priyadharshini et al, 35 (17.5%), Mani et al, 37 (29%) and Pradeep kumar et al, 36 (50.0%). The percentage of encounters with injection is 12% which is within the range of WHO value (<20%) but lower than the study conducted by Mani et al, 37 (48%).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…A study conducted in a hospital in southern India revealed that 69% of drugs were from the essential drug list. [ 25 ] The prescriptions had no injection prescribed since the prescriptions were collected from a pharmacy dispensing outpatient department prescriptions.…”
Section: Discussionmentioning
confidence: 99%